A descriptive Study on Uterine Compression U-sutures to Control Postpartum Hemorrhage with fertility Preservation: A Simple and Effective Technique - Khatun, Mst Rokeya; Shahela, Jesmin (TAJ: Journal of Teachers Association, 2018)
Objective: This study evaluated the effectiveness of a modified U-suturing technique in effecting uterine compression in patients with atonic primary postpartum hemorrhage (PPPH), which does not respond to manual compression or drugs. Method: We retrospectively reviewed the charts of all patients who delivered between 2013 and 2015 at Gynae & Obstetrics Department of Rajshahi Medical College Hospital and who underwent uterine compression sutures for PPPH and results of a follow-up and questionnaire were evaluated and our experience with this method was reviewed. Results: Fifty two women had uterine compression U sutures for P PPH. The mean age of the patients was 24±2.2 years. The mean gestational age at delivery was 38.2±2.3 weeks, and the average estimated blood loss was 2.3±2.1 L. The mean procedure time to perform the uterine compression U sutures was 11.5±2.8 minutes. None of the 52 patients required hysterectomy. Conclusion: Uterine compression U-sutures technique is an easily and rapidly applied, effective, simple, safe & life saving method for the treatment of PPPH, thus avoiding hyterectomy and preserving potential fertility. TAJ 2013; 26: 67-73